Comparison of influence of surfactants on thermokinetic characteristics of alkali-activated slag cement - Krivenko Pavlo; Rudenko Igor; Konstantynovskyi Oleksandr (Private Company Technology Center, 2021)
Increasing the durability of concrete and reinforced concrete structures according to the criterion of crack resistance is a relevant task of construction materials science. To solve this task, this paper proposes effective solutions for adjusting thermofinite characteristics of alkali-activated slag cement (ASC) by using surfactants of various chemical nature in order to control the thermally-stressed state of concrete based on it (ASC concrete). The method of calorimetry was applied to show that the problematic issue is to adjust the structure formation of ASC by anion-active surface-active substances based on complex polyesters. This is predetermined by the instability of the molecular structure of surfactants in the hydration environment of ASC due to the destruction of complex ester bonds as a result of alkaline hydrolysis. Thermokinetic analysis has demonstrated the effectiveness of using anion-active surfactants, which do not contain ester bonds, as regulators of crack resistance of ASC concrete. Simple polyesters and multi-atom alcohols provide the ability to adjust the duration of the induction period while ensuring the required completeness of ASC hydration within a time frame. The effectiveness of cation-active surface-active substances has been shown, which are characterized by the stability of the molecular structure in the hydration environment of ASC and an increased level of adsorbing capacity. The decrease in the effectiveness of surface-active substances has been shown, in terms of the effect on the heat release of ASC, in the following series: alkaline salt of carboxylic acid>salt of the quaternary ammonium compound>simple polyester> polyalcohol>complex polyester. The reported results are important in view of the possibility of effective adjustment of ASC heat release by influencing the structure formation of surfactant with a certain molecular arrangement in order to predictably reduce crack formation in a thermally-stressed state and a corresponding increase in the durability of structures.
Keywords: alkali-activated slag cement; surfactant; crack resistance; heat release of cement slurry; thermallystressed state; пар; лужноактивований шлаковий цемент; 666.9